Preiskava pljučne funkcije pri otrocih - Fležar, Matjaž (Zdravniški vestnik, 2004)
Background. Lung function testing in children above five years old is standardised similarly as is in adult population (2). Nevertheless bronchial provocation testing can be more hazardous since the calibre and reactivity of childhood airway is different. We analysed the frequency of different lung function testing procedures and addressed the safety issues of bronchial provocation testing in children. Methods. We analysed lung function testing results in 517 children, older than 5 years, tested in our laboratory in threeyear period. Spirometry was done in every patient, metacholine provocation test was used as a part of diagnostic work-up in suspected asthma.In case of airway obstruction, bronchodilator test with salbutamol was used instead of a metacholine provocation test. Results. The most common procedure in children was spirometry with bronchial provocation test as a partof diagnostic work-up of obstructive syndrome (mostly asthma). 292 children required metacholine test and 253 tests were interpreted as positive.The decline in expiratory flows (forced expiratory flow in first second - FEV1) in positive tests was greater than in adult population as was the dose of metacholine, needed to induce bronchoconstriction. The compliance of children was better than in adults. Conclusions. Lung function testing in children is reliable and safe and can be done in a well-standardised laboratory that follows the regulations of such testing in adults.
Keywords: Adolescenca; Adolescence; bolezni; Bronchial Provocation Tests; Bronhialni, provokacijski testi; Child; Diagnostic Use; diagnostika; disease; Forced Expiratory Volume; Forsirani, ekspiratorni volumen; Lung Volume Measurements; Metaholinski klorid; Methacholine Chloride; otroci; Otrok; pljuča; Pljučni volumen, meritve; Spirometrija; Spirometry; Vital Capacity; Vitalna kapaciteta